Pengembangan Ekonomi Kreatif di Kota Tarutung Melalui UMKM Kain Tenun Ulos - Putri Kemala Dewi Lubis; Rafli Rafli; Samuel Tobing; Debora Tarigas Marpaung (Jurnal Ekonomi-Qu, 2023)
The purpose of this study is to determine the creative economy development of Tartun City by UMKM Ulos Woven Fabrics. This study is a qualitative descriptive study systematically explained and clearly presented. Data collection techniques are performed. By observing and studying the literature for several articles related to the development of the creative industries. Since the method of research conducted here is a literature search or literature search, here we will examine several sources, both scientific papers on the creative industries and several Internet sources related to UMKM, which we are currently studying. We search the literature sources of Based on his SWOT analysis observations above, we can see that there are some problems in the development of Dameuros SMEs in Tartun city that need to be minimized. By updating the previously used strategy. Another example of strategy is using technology as a broad promotional tool. With more widely available marketing and advertising technology, product information and ideas become more relevant.